Manajemen Kompetensi Profesional Guru al-Quran Hadits di Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng - Nurfuadi Nurfuadi (Journal on Education, 2023)
Teacher competence is an important aspect in the implementation of education in schools or madrasas. The purpose of this paper is to analyze how the professional competency management of Al-Quran Hadith teachers at Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng. This research is qualitative with the results of the study namely the Qur'an Hadith subject technically the implementation of the teacher entering the class conveys material using the Hadith story model about maintaining/restraining lust or anger by linking life in the community around us an example when the teacher delivers material about Hifdun Nafs (maintaining lust) then it is also exemplified about children who like to be insulted by bad names by their friends, but the child who is insulted is not provoked or angry. For the 11th grade learning model, first the students and the teacher enter and then pray together, then the teacher opens with a greeting after that the teacher appoints one of the student groups to present the results of the group discussion which at the previous meeting had already been formed.